Model Partisipatif Pengelolaan Pariwisata Bahari oleh Masyarakat Bajo di Pulau Labengki - Nana Adriana Hutari; Ashar Hasyim; Andi Resmiyanti (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The participatory communication model in marine tourism management can be used as a reference in managing marine tourism that maximally involves community participation. The community must be involved in marine tourism management. Community participation is important because the community in tourism management is positioned as an 'object of tourism management' rather than a 'subject of tourism management.' This study focuses on the participatory communication model of the Bajo community in marine tourism management on Labengki Island. The research findings indicate that participatory communication of the Bajo community in marine tourism management is carried out through various activities. The Bajo community participates in planning, management, decision-making, and evaluation of tourism management activities. In addition, community empowerment in managing marine tourism on Labengki Island can be seen with the existence of homestays owned and managed by the Bajo community to support tourism. The Bajo community is also involved in providing tourism transportation, specifically boats, thereby improving the local economy. The Bajo community receives training from the government in managing homestays, becoming tour guides, and maintaining the tourism environment on Labengki Island.